A COMPARATIVE CLINICAL STUDY TO EVALUVATE THE EFFECT OF HARIDRADI GANA CHURNA AND TRIPHALA CHURNA UDVARTANA IN STHOULYA (OBESITY) - Chaitra lakshmi K N; Basarigidad, Jairaj P (International Journal of Ayurveda and Pharma Research, 2019)
In the present century due to the busy and sedentary life people open the gate to welcome numerous diseases. Sthoulya is one among the major diseases that falls under the category of Santarpanottha vyadhi. The term overweight and obesity refers to body weight that is greater than what is considered healthy for a certain height. Sthoulya is mainly caused by Kapha, Vata Doshas and Meda Dhatu. Udvartana has better results in the management of Sthoulya, as it does Kapha-Vatahara, Medo vilayana. So, the present has been conducted to compare and evaluate the effect of Haridradi gana Churna and Triphala Churna Udvartana in Sthoulya. The study has been conducted in two groups with 20 patients each. One with Haridradi gana Churna and other group with Triphala Churna which are Kapha-Medahara & Kapha-Pramehahara respectively because of Laghu, Ruksha & Ushna properties. The present study concludes saying Haridradi gana Churna showed better results than Triphala Churna.